TRANSFORMASI KONSEP HAK IJBAR ORANG TUA: DARI FIQIH KLASIK KE REALITAS HUKUM MODERN - Amal Zainun Naim; Hustina (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
This article examines the transformation of the concept of ijbar (parental authority in marriage) in Islamic family law, from its classical fiqh construction to contemporary legal realities, amid growing concern over child marriage and marriages conducted without genuine consent in religious court proceedings. In classical fiqh, ijbar is understood as the guardian’s—particularly the father’s—authority to arrange a child’s marriage in the name of perceived welfare, even without explicit consent. In modern legal contexts, however, this concept raises serious concerns when the consent of female marriage candidates is still interpreted through silence. Employing a normative-juridical approach, this study compares classical fiqh doctrines, positive law, and a maqasid al-shariah perspective. The findings reveal a persistent gap between legal reforms that emphasize consent and judicial practices that continue to rely on passive consent. Such practices risk perpetuating unequal power relations and enabling subtle forms of coercion. This article argues for clearer normative guidance to ensure that marital consent is obtained freely and consciously. By prioritizing human dignity and individual autonomy, this study contributes to strengthening Islamic family law reform in line with principles of justice and maqasid al-shariah. Keywords: Ijbar Right, Family Fiqh, Maqasid al-Shariah